BASIC DIMENSIONS OF THE (SERVQUAL MODEL) AND ITS IMPACT ON THE LEVEL OF CUSTOMER SATISFACTION: AN EMPIRICAL STUDY OF THE HOUSING BANK IN KARAK, JORDAN - Sulieman, Aymn (European Scientific Journal, ESJ, 2013)
The objective of this study is to identify the impact of the basic dimensions of the (SERVQUAL model) on the level of customer satisfaction in dealing with the Housing Bank, to achieve the objectives of the study; an improved questionnaire have been used for the purpose of data collection and distributing it to the (375) sample members, Statistical package for Social Sciences (SPSS) have been used the for data analysis of the questionnaire. The study found that: There is an impact of the basic dimensions of the (SERVQUAL model) on the level of customer satisfaction at different levels. The study recommends the need for continuous improvement of services provided to customers, through consumer behavior studies, and work to predict customer expectations to ensure the provision of better services.